2010
DOI: 10.1177/1087054710376907
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Atomoxetine in Children With Severe Autistic Disorders and Symptoms of ADHD

Abstract: Atomoxetine did not benefit children with severe autistic disorder who have ADHD symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 21 publications
(26 reference statements)
0
35
1
Order By: Relevance
“…This similar efficacy of atomoxetine in children with autistic disorder is in contrast with a small-scale open-label study showing no benefits of atomoxetine treatment in 12 children with a severe form of autistic disorder and ADHD symptoms (Charnsil 2011).…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…This similar efficacy of atomoxetine in children with autistic disorder is in contrast with a small-scale open-label study showing no benefits of atomoxetine treatment in 12 children with a severe form of autistic disorder and ADHD symptoms (Charnsil 2011).…”
Section: Discussioncontrasting
confidence: 68%
“…2006;Charnsil 2011;Zeiner et al 2011;Fernández-Jaén et al 2013) have suggested that atomoxetine, a noradrenergic reuptake inhibitor, might be a promising treatment for ADHD symptoms in children and adolescents with ASD. We have confirmed these preliminary findings in a double-blind placebo-controlled trial followed by an open-label extension period in children and adolescents with ASD and concomitant ADHD symptoms, and have demonstrated superior efficacy of atomoxetine compared with placebo, as rated by the investigator-administered ADHD-Rating Scale (ADHD-RS), with good tolerability (Harfterkamp et al 2012).…”
mentioning
confidence: 99%
“…Positive results for atomextine are more evident among children with ASD who are cognitively higher functioning (defined as IQ >70) [45]. In a separate investigation, atomoxetine treatment yielded no observed symptom reduction in a sample of children with high ASD symptom severity [46].…”
Section: Nonstimulant Medicationsmentioning
confidence: 89%
“…A great number of studies showed its effectiveness on irritability, aggressive behavior, short span of attention, increased impulsivity and hyperactivity [23,24]. Nevertheless, there was not any recent study in connection with atomoxetine treatment in MPS cases whose hyperactivity and impulsivity symptoms were prominent.…”
Section: Discussionmentioning
confidence: 99%